حماية منصات التعليم عن بعد من منظور الفقه الإسلامي: دراسة فقهية مقارنة - عيسى، محمود عبدالعظيم علي (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2024)
بات نظام التعليم عن بعد أسلوباً حديثاً ذا قيمة عند كثير من المؤسسات التعليمية؛ لذا اتجهت كثير من الدول لتفعيله، لا سيما بعد هذا التقدم التقني الذي يشهده العالم يوما تلو الآخر. وقد قامت هذه المؤسسات التعليمية- في سبيل تفعيل هذا النظام- بإنشاء ما يعرف بمنصات التعليم عن بعد، والتي تعتبر بيئة تعلم افتراضية عبر الشبكة العنكبوتية تسمح للمعلمين بإنشاء فصول دراسية افتراضية تعمل على توفير خبرات تعلم تشاركية وتبادل الخبرات بطريقة تفاعلية وتمكن مستخدميها من التجمع في كيانات اجتماعية تشبه الكيانات الواقعية فيما يسمى بمجموعات العمل. لذا تناولت في هذا البحث عرضاً لمفهوم منصات التعليم عن بعد وأنواعها. كما بينت ما قد تتعرض له هذه المنصات التعليمية من أشكال متنوعة من الاعتداء في صورة اختراق عبر الشبكة العنكبوتية يتم من خلاله إتلاف للمحتوى التعليمي الكائن على المنصة. وقد يكون هذا الاعتداء في صورة سرقة لهذا المحتوى التعليمي وبيعه بغية التربح من ورائه. كما أوضحت ما وضعه الفقهاء من التدابير والعقوبات الرادعة لأشكال الاعتداء على منصات التعليم عن بعد. Distance learning has become a valuable modern method for many educational institutions. Therefore, many countries have turned to it, especially after the technological progress that the world is witnessing day after day. In order to activate this system, these educational institutions have created what is known as distance learning platforms, which are considered a virtual learning environment over the Internet that allows teachers to create virtual classrooms that provide shared learning experiences and exchange experiences in an interactive way, and enable its users to gather in social entities similar to real entities in what is called workgroups. Therefore, this research presented the concept of distance learning platforms and their types. It also showed the various forms of attacks that these educational platforms may be exposed to, in the form of hacking through the Internet, through which the educational content on the platform is destroyed. This attack may take the form of stealing this educational content and selling it for the purpose of profit from it. It also explained the measures and deterrent penalties that the jurists have put in place for the forms of attacks on distance learning platforms.
Keywords: الفقه الإسلامي -- التعليم الإلكتروني -- المنصات التعليمية -- الأمن السيبراني